Effect of relaxin on motility, acrosome reaction and viability of cryopreserved boar spermatozoa - MIAH, ABDUL GAFFAR (Reprod Med Biol, 2006)
Background and Aims:   Relaxin has an important role in stimulating motility and the acrosome reaction (AR) of fresh boar spermatozoa. The objective of the present study was to determine whether relaxin can improve the motility, AR and viability of cryopreserved boar spermatozoa. Methods:   Cryopreserved boar spermatozoa were thawed, washed and incubated at 37°C for 4 h in modified Beltsville thawing solution supplemented with 0, 20 or 40 ng/mL relaxin. Sperm motility, AR, viability, and incorporation and oxidation of (14)C‐glucose were evaluated during 0–4 h of incubation. Results:  The results show that the supplementation of relaxin (especially at 20 ng/mL) in the thawing solution improved sperm motility significantly (P < 0.05) at 1–3 h of incubation. The percentage of acrosome reacted live spermatozoa was improved significantly (P < 0.05) when the spermatozoa were treated with 20 ng/mL relaxin. Viability was not significantly (P > 0.05) improved by supplementation with relaxin. The rates of incorporation and oxidation of (14)C‐glucose were increased in correlation with AR up to 4 h of incubation. Conclusion:  We conclude that relaxin can improve the sperm motility and AR, and enhance the glucose metabolism of cryopreserved boar spermatozoa. (Reprod Med Biol 2006; 5: 215–220)